Corrosion fatigue behavior of FV520B steel in water and salt-spray environments. (September 2017) - Wu, Qaioguo; Chen, Xuedong; Fan, Zhichao; Nie, Defu; Wei, Renchao
Abstract: The corrosion fatigue behavior of FV520B steel in water and salt-spray environments at different temperatures is the focus of this study. Temperature has a significant effect on the fatigue behavior of FV520B steel in water and salt-spray environments, but has only a negligible effect in an air environment. Fatigue life decreases as temperature increases in water and salt-spray environments, and this trend is much more remarkable at a low stress amplitude level. As compared to air and water-spray, it was found that the chloride ion in salt-spray accelerated the fatigue damage of FV520B steel. Micro observation revealed that the fatigue cracks were initiated on the surfaces of the specimens in all experimental environments, and significant evidence of corrosion pits and micro cracks was found on the surfaces of the specimens in the salt-spray environment. Based on the pitting corrosion mechanism, a modified fatigue life prediction model that considered the combined effects of stress, temperature and corrosion was proposed. The study results show that the model predictions are in good agreement with the test data. Highlights: Experimental study on corrosion fatigue behavior of FV520B steel was conducted. Change laws of fatigue behavior with corrosion media and temperatures were analyzed. Fatigue crack initiation mechanisms were discussed by micro observations. Fatigue life prediction model based on pitting corrosion mechanism was proposed.